2010
DOI: 10.1073/pnas.1012667107
|View full text |Cite
|
Sign up to set email alerts
|

Müllerian inhibiting substance preferentially inhibits stem/progenitors in human ovarian cancer cell lines compared with chemotherapeutics

Abstract: Cancer stem cells are proposed to be tumor-initiating cells capable of tumorigenesis, recurrence, metastasis, and drug resistance, and, like somatic stem cells, are thought to be capable of unlimited selfrenewal and, when stimulated, proliferation and differentiation. Here we select cells by expression of a panel of markers to enrich for a population with stem cell-like characteristics. A panel of eight was initially selected from 95 human cell surface antigens as each was shared among human ovarian primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 58 publications
8
84
2
2
Order By: Relevance
“…We recently identified a CD44+, CD24+, Epcam+ (3+) population, selectable by flow cytometry, which is enriched for stem/progenitor cells (5). When combined with negative selection for Ecadherin (3+Ecad−), the resulting smaller population consistently formed more and larger colonies [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently identified a CD44+, CD24+, Epcam+ (3+) population, selectable by flow cytometry, which is enriched for stem/progenitor cells (5). When combined with negative selection for Ecadherin (3+Ecad−), the resulting smaller population consistently formed more and larger colonies [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The production of purified, fully cleaved AMH has been achieved only recently, 51 and with this AMH one would need only 1:1000 of the dose compared with partially cleaved AMH. Targeting AMHRII with activating antibodies 62 or small molecule agonists 23,59 presents another attractive option for supplementary treatment of AMHRII-positive advanced or recurrent GCTs. Nevertheless, the observed activation of apoptosis in GCTs may not necessarily involve AMHRII, given that the doses used in this study are more robust than implicated by the reported K d for AMH to AMHRII.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Ovarian epithelial carcinoma cells, originating from the coelomic epithelium/Müllerian duct, express AMHRII 17 and AMHRII positivity is also associated with prolonged overall survival. 19 AMH has been indicated as a growth inhibitor of AMHRII-positive ovarian cancer cells in vitro [20][21][22][23] and in vivo, [24][25][26][27] and this growth-inhibitory effect is characterized by a block in the cell cycle progression and subsequent apoptosis. 20,22 Although AMH has been indicated as a tissue marker for GCTs, 28 AMH immunoreactivity in a series of 80 primary GCTs was low or negative in the tumors larger than 10 cm in diameter.…”
mentioning
confidence: 99%
“…Cancer stem cells differ from their non-stem cancer cell counterparts in a wide variety of measurable properties, some of which include: proliferation rate (Moore and Lyle, 2011), migratory and invasive behavior (Wei et al, 2010), metastatic potential , and DNA repair activation/mechanisms (Bao et al, 2006a).…”
Section: Heterogeneitymentioning
confidence: 99%